Erratum for: Single‐layer polarization‐switchable frequency‐band‐fixed microstrip antenna using a single‐switch. Issue 11 (27th August 2014) - Oh, Soon‐Soo; Park, Wook‐Ki; Ahn, Chi‐Hyung; Shafai, Lotfollah
ABSTRACT A single‐layer polarization‐switchable frequency‐bandfixed microstrip square‐ring antenna was developed. The copolar plane of the radiation pattern was reconfigured with a single‐switch, but the resonant frequencies were identical. A microstrip square‐ring antenna was adopted, and the lateral and vertical widths of the microstrip ring were tuned to agree the resonant frequencies of the unloaded or loaded antenna. A single‐layer dielectric substrate was used instead of a latest three‐layer configuration. Antenna impedance was optimized to a value between those of the loaded and unloaded antennas. The proposed antenna exhibited single‐switch polarization–reconfiguration on a single‐layer substrate, and could thus be used in mobile communications and microwave imaging systems. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:1874–1879, 2014